STEAM METHODOLOGY AND ENGLISH IN PRESCHOOL EDUCATION. (Western European Journal of Modern Experiments and Scientific Methods, 2025)
The introduction of the STEAM (science, technology, engineering, art, mathematics) approach into preschool English lessons is gaining increasing attention. The reason for this is that educators are looking for methods that develop not only linguistic knowledge, but also creativity, problem-solving, cooperation, and scientific thinking. Traditional preschool English lessons are often based on memorization, repetition, and individual word learning exercises, which do not fully meet the developmental needs of modern younger students. This article analyzes recent research (2010-2024) on the application of STEAM principles in teaching English as a primary foreign language (EFL). Based on a review of high-quality literature, practical experiences, research-based tasks, education in harmony with art, engineering problems, and how mathematical reasoning support language learning are explored. The results show that English lessons based on STEAM provide deeper understanding, increase interest, strengthen vocabulary, and develop 21st-century skills. In conclusion, STEAM is an effective and appropriate method for the development of children for teaching English in preschool educational institutions.